Analysis of Depth-based and Diffusion Model-based Toon Shading in 3D and 2D Rendering - Huang, Shiming (Transactions on Computer Science and Intelligent Systems Research, 2025)
This paper explores toon shading, a rendering technique widely applied to 3D models to create cartoon or anime-style visuals characterized by flat surfaces and shadows. While toon shading can also be used at the 2D level, it is less common and not as broadly applicable compared to its 3D counterpart. This paper aims to review existing toon shading methods and assess their efficiency in stylization and overall product quality. Specifically, this paper examines depth-based toon shading, which utilizes distance information related to light sources, viewports, geometry, and orientations to group polygons in a desired configuration. Additionally, the paper discusses a newly developed toon shading method using diffusion models. The analysis concludes that current toon shading methods effectively achieve stylized surface coloring and shadow effects central to the cartoon aesthetic. Furthermore, the paper advocates for future research into modifying line-art, enhancing non-photorealistic abstraction, and hand-drawn styles. This research could bridge the gap between 2D and 3D applications, benefiting the animation and gaming industries by improving the integration of toon shading techniques across various production pipelines.